Necesidad de reformar el art. 8 de la Ley de pasantías en el sector empresarial, por cuanto se vulnera el derecho a la igualdad de condiciones y oportunidades establecidas en la Constitución - Tapia Ruíz, Luis Wuinther (2015)
Without place to doubt the Constitution of the 2008, believe new horizons therefore on the guarantee of the rights that you/they will prevail on any juridical other classification, the norms and the acts of the public power will maintain conformity with the constitutional dispositions. Such it is the case of the Law that regulates the Internships in the Managerial Sector, on the inclusion to the companies of the private sector of the students or students registered in the second or superior years of the Centers of Studies of Superior level, in Art. 8 on the control determine that the number of passing will take like base the declaration or payment of the schedule that he/she makes the company to the Ecuadorian Institute of Social security (IESS). But this norm is not clear since it doesn't determine that exact percentage should take into account for the labor insert of the students' of the different centers of studies of superior level practices pre-professional, stopping to the free will to the directive of the companies of the private sector to make the decision of intruding or not to the studying gentlemen so that they carry out its practices pre-professionals. In such a sense this harms the right to the equality of conditions and opportunities guaranteed in the Constitution and therefore it lacks artificial effectiveness, when not being clear and concise. Taking into account that the inclusion of practical pre-labor in the managerial sector, he/she would cooperate to acquire knowledge, dexterity and experiences to the students for an efficient development in the professional exercise